Artificial intelligence (AI) vs human accountant / Nazirah Naiimi and Salwana Selamat - Naiimi, Nazirah; Selamat, Salwana (Fakulti Perakaunan, 2023)
Artificial Intelligence (Al) has taken control of a significant part of accountants' tasks. According to Leitner H, S. et al. (2021), Al-based technologies such as intelligent robots, automated tools and business intelligence tools have to replace humans as actors and transform processes in accounting. The most affected tasks are data entry, transaction processing, and basic bookkeeping. Al-powered software can, for example, automatically categorize and record financial transactions, process invoices, and reconcile accounts, reducing the need for manual data entry and repetitive tasks. AI-driven data analytics tools can also analyze large datasets, identify patterns, and generate financial reports more efficiently than traditional methods. As a result, accountants can focus on higher-level tasks, such as financial analysis, strategic planning, and providing valuable insights to clients or stakeholders.